Cryptic Species of Freshwater Sculpin (Cottidae: Cottus) in California, USA - Moyle, Peter B.; Campbell, Matthew A. (Zootaxa, 2022)
The Riffle Sculpin (Cottus gulosus) is a small, bottom-dwelling fish regarded as widespread in the cool-water streams that flow into California’s Central Valley and into streams of the central California coast. Using population genomics, supported by other genetic, distributional, and meristic studies, we demonstrate that C. gulosus consists of three cryptic species with four subspecies (five lineages), all but one entirely endemic to California: Cottus pitensis, Pit Sculpin Bailey and Bond 1963 Cottus gulosus, Inland Riffle Sculpin (Girard 1854) g. gulosus: San Joaquin Riffle Sculpin (Girard 1854), nominate subspecies g. wintu: Sacramento Riffle Sculpin, Moyle and Campbell 2022, new subspecies Cottus ohlone, Coastal Riffle Sculpin Moyle and Campbell 2022, new species o. ohlone, Ohlone Riffle Sculpin Moyle and Campbell 2022, nominate subspecies o. pomo, Pomo Riffle Sculpin Moyle and Campbell 2022, new subspecies. The three species are endemic to California watersheds although the range of C. pitensis extends into southeastern Oregon. All are confined to cool headwater streams or to rivers with cold water releases below dams. Their populations are increasingly isolated from one another because of anthropogenic changes to California’s river systems and some are threatened with extinction. Providing taxonomic recognition of the distinct forms will improve conservation efforts on their behalf. This study also demonstrates how genomics can be used to resolve situations where signals from mitochondrial and nuclear DNA are in conflict.